A feasibility and usability study of a virtual reality tool (VESPA 2.0) for cognitive rehabilitation in patients with mild cognitive impairment: an ecological approach - Latella, Desirèe; Formica, Caterina; Ielo, Augusto; Grioli, Pietro; Marra, Angela; Costanzo, Daniela; Merlo, Maria Emanuele; Pappalardo, Salvatore Marco; Corallo, Francesco; Marino, Silvia; Quartarone, Angelo; Calabrò, Rocco Salvatore; et al. (Frontiers in Psychology, 2024)
Dear Editor, I am writing to submit my manuscript titled "Efficacy of Virtual Reality Tool (VESPA 2.0) for Cognitive Rehabilitation in Patients with Mild Cognitive Impairment" for consideration for publication in your esteemed journal. It focuses on cognitive rehabilitation application development designed for patients with mild cognitive impairment (MCI). I want to emphasize the relevance and significance of my study to your journal for several reasons: -This study aligns with the context of virtual reality for cognitive rehabilitation, an area of growing interest for researchers and healthcare professionals. VESPA 2.0 offers an approach to addressing challenges with MCI, making a significant contribution. -VESPA 2.0 integrates scientifically validated methodologies with digital tools, providing a personalized, flexible, and ecological approach to managing MCI. -Our findings offer important practical implications for healthcare professionals. The evidence supports the proposed application's effectiveness and utility, offering new rehabilitative treatment perspectives to improve the quality of life and well-being of MCI. -Scientific research focused on praecox diagnosis and individualized risk factors of this clinical condition. Still, rehabilitation plays a crucial role in maintaining cognitive skills in the absence of efficacious drug therapies. This study could provide evidence and perspectives on the cognitive rehabilitation area. Sincerely, Caterina Formica